V+4-8=6(v+7)+2(v+5)

Simple and best practice solution for V+4-8=6(v+7)+2(v+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for V+4-8=6(v+7)+2(v+5) equation:


Simplifying
V + 4 + -8 = 6(v + 7) + 2(v + 5)

Reorder the terms:
4 + -8 + V = 6(v + 7) + 2(v + 5)

Combine like terms: 4 + -8 = -4
-4 + V = 6(v + 7) + 2(v + 5)

Reorder the terms:
-4 + V = 6(7 + v) + 2(v + 5)
-4 + V = (7 * 6 + v * 6) + 2(v + 5)
-4 + V = (42 + 6v) + 2(v + 5)

Reorder the terms:
-4 + V = 42 + 6v + 2(5 + v)
-4 + V = 42 + 6v + (5 * 2 + v * 2)
-4 + V = 42 + 6v + (10 + 2v)

Reorder the terms:
-4 + V = 42 + 10 + 6v + 2v

Combine like terms: 42 + 10 = 52
-4 + V = 52 + 6v + 2v

Combine like terms: 6v + 2v = 8v
-4 + V = 52 + 8v

Solving
-4 + V = 52 + 8v

Solving for variable 'V'.

Move all terms containing V to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + V = 52 + 4 + 8v

Combine like terms: -4 + 4 = 0
0 + V = 52 + 4 + 8v
V = 52 + 4 + 8v

Combine like terms: 52 + 4 = 56
V = 56 + 8v

Simplifying
V = 56 + 8v

See similar equations:

| 8(x-7)=-112 | | -12-11d=-10d | | ax+bx=-4 | | X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 | | -5+b/8=-4 | | -7(x+3)=3(-5-2x) | | 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x | | X-4y=3b | | 3(x-1)=2x-3+3 |

Equations solver categories